Long-Term Effects of Traumatic Brain Injury on Anxiety-Like Behaviors in Mice: Behavioral and Neural Correlates - Popovitz, Juliana; Mysore, Shreesh P.; Adwanikar, Hita (Frontiers in Behavioral Neuroscience, 2019)
Traumatic brain injury has been frequently linked to affective disorders such as anxiety and depression. However, much remains to be understood about the underlying molecular and signaling mechanisms that mediate affective dysfunctions following injury. A lack of consensus in animal studies regarding what the affective sequelae of TBI are has been a major hurdle that has slowed progress, with studies reporting the full range of effects: increase, decrease, and no change in anxiety following injury. Here, we addressed this issue directly by investigating long-term anxiety outcomes in mice following a moderate to severe controlled cortical impact injury using a battery of standard behavioral tests - the open field, elevated zero maze, and elevated plus maze. Mice were tested on weeks one, three, five and seven post-injury. Our results show that the effect of injury is time- and task-dependent. Early on – up to 3 weeks post-injury, there is an increase in anxiety-like behaviors in the elevated plus and zero mazes. However, after 5 weeks post-injury, anxiety-like behavior decreases, as measured in the open field and elevated zero maze. Immunostaining in the basolateral amygdala for GAD, a marker for GABA, at the end of the behavioral testing showed the late decrease in anxiety behavior was correlated with upregulation of inhibition. The approach adopted in this study reveals a complex trajectory of affective outcomes following injury, and highlights the importance of comparing outcomes in different assays and time-points, to ensure that the affective consequences of injury are adequately assessed.